1986
DOI: 10.1145/17356.17397
|View full text |Cite
|
Sign up to set email alerts
|

Warp architecture and implementation

Abstract: A high-performance systolic array computer called Warp has been designed and constructed. The machine has a systolic array of 10 or more linearly connected cells, each of which is a programmable processor capable of performing 10 million floating-point operations per second (10 MFLOPS). A 10-cell machine therefore has a peak performance of 100 MFLOPS. Warp is integrated into a UNIX host system. Program development is supported by a compiler.The first 10-cell machine became operational in 1986. Low-level vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…But their lack of programmability restricts their flexibility. Efforts to produce programmable systolic arrays (e.g., the CMU WARP [1] [8]) produced systems more akin to MIMD architectures (see Section 5) than those described here. Systolic architecture are well suited for dedicated high throughput computation such as image compression.…”
Section: Systolic Array Architecturesmentioning
confidence: 99%
“…But their lack of programmability restricts their flexibility. Efforts to produce programmable systolic arrays (e.g., the CMU WARP [1] [8]) produced systems more akin to MIMD architectures (see Section 5) than those described here. Systolic architecture are well suited for dedicated high throughput computation such as image compression.…”
Section: Systolic Array Architecturesmentioning
confidence: 99%
“…signal processing, and scientific computing have been written to date [3]. This study is based on the prototype Warp cell [2] which is described next. The production version which incorporates some improvements over the prototype has become available only recently [4].…”
Section: Background On Warpmentioning
confidence: 99%
“…When equipped with a local memory, these processors are powerful computing engines. Research in systolic systems has demonstrated that an array built from high-performance programmable processors can deliver high computation bandwidth [ 1].…”
Section: Introductionmentioning
confidence: 99%